Fisheries education in Sri Lanka: current status, constraints and future outlook - Bandara, Tharindu; Radampola, Kumudu (Journal of Fisheries, 2017)
Sustainable utilization of the fishery resources along with manpower is one of the most important aspects of fisheries science. Although a huge manpower is available in the fisheries sector, lapses in knowledge also prevalent in various subsections of fishery related occupations. In this scenario, this paper attempts to evaluate the various levels of fisheries education in Sri Lanka. It has been observed that clear demarcation of the level of fisheries education such as undergraduate, postgraduate, and basic level exists in Sri Lanka. Although a low level of student enrolment, university education of fisheries and aquaculture is at satisfactory level. Expansion of fisheries education for basic levels such as education of fisherwomen needs to be improved. Scientific dissemination of knowledge by published works such as journals should further be expanded and indexing of those journals in reputable and reliable databases is needed. Several constraints in Sri Lankan fisheries education such as inadequate funding, low level of student enrolment, quality of the students and less cooperation with industries etc. were also identified. Therefore, finding possible solutions to these issues is necessary to ensure the quality of the education in Sri Lanka.